A Two-stage Approach for Rapid Assessment of the Proportion Achieving Viral Suppression Using Routine Clinical Data. Issue 5 (30th May 2022) - Edwards, Jessie K.; Donastorg, Yeycy; Zadrozny, Sabrina; Hileman, Sarah; Gómez, Hoisex; Seamans, Marissa J.; Herce, Michael E.; Ramírez, Edwin; Barrington, Clare; Weir, Sharon
Abstract : Background: Improving viral suppression among people with HIV reduces morbidity, mortality, and transmission. Accordingly, monitoring the proportion of patients with a suppressed viral load is important to optimizing HIV care and treatment programs. But viral load data are often incomplete in clinical records. We illustrate a two-stage approach to estimate the proportion of treated people with HIV who have a suppressed viral load in the Dominican Republic. Methods: Routinely collected data on viral load and patient characteristics were recorded in a national database, but 74% of patients on treatment at the time of the study did not have a recent viral load measurement. We recruited a subset of these patients for a rapid assessment that obtained additional viral load measurements. We combined results from the rapid assessment and main database using a two-stage weighting approach and compared results to estimates obtained using standard approaches to account for missing data. Results: Of patients with recent routinely collected viral load data, 60% had a suppressed viral load. Results were similar after applying standard approaches to account for missing data. Using the two-stage approach, we estimated that 77% (95% confidence interval [CI] = 74, 80) of those on treatment had a suppressed viral load. Conclusions: When assessing the proportion of people on treatment with a suppressed viral load using routinely collected data, applying standard approaches to handle missing data may be inadequate. In these settings, augmenting routinely collected data with data collected through sampling-based approaches could allow more accurate and efficient monitoring of HIV treatment program effectiveness.